2012
DOI: 10.1177/0266666911417642
|View full text |Cite
|
Sign up to set email alerts
|

Role of information for rural development in Bangladesh: a sector-wise review

Abstract: Although it is generally agreed that information plays a critical role in development, no sure-success way of applying information for sustainable development has been worked out so far. This article gives an overview of the roles information could play in various socio-politico-economic sectors in the rural areas of Bangladesh. Against a backdrop of the enactment of a Right to Information Act and the government’s recent efforts towards establishing a Digital Bangladesh by the year 2021, the country has been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The librarian or information worker can assist the patrons by acting as a facilitator in such programmes. This includes providing useful information and making important texts available to encourage people to read, especially those in the rural communities (Hoq, 2012). Outreach programmes.…”
Section: Poverty Alleviation Programmes In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…The librarian or information worker can assist the patrons by acting as a facilitator in such programmes. This includes providing useful information and making important texts available to encourage people to read, especially those in the rural communities (Hoq, 2012). Outreach programmes.…”
Section: Poverty Alleviation Programmes In Nigeriamentioning
confidence: 99%
“…Examples can be taken from China, where their existence was reported by Clarke et al (2011). Also, according to Hoq (2012), a rural information centre that is run by an able information professional can educate the rural people on how to make the best use of their money and resources, as well as providing information on jobs and ways of getting them. Library and information entrepreneurship programmes and schemes.…”
Section: Poverty Alleviation Programmes In Nigeriamentioning
confidence: 99%
“…Counter-trafficking organizations have reached their target audience: rural residents, people from lower social classes, and less education are more informed about human trafficking. Despite the organizations' assumptions, another study also found that accurate information can empower rural people with knowledge on human rights, health, and employment, among others (Hoq 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Information serves as the basis for any development activity (FAO and World Bank, 2000; Tadesse, 2008). In addition, in the agricultural sector, making relevant, reliable and useful information available to producers at the right time can significantly contribute to increasing agricultural productivity (Tadesse 2008; Demiryürek 2010; Hoq 2012; Rehman et al 2013). Norton (2005) argues that for extension services to achieve their agricultural and rural development objectives, the availability and flow of good quality information are important.…”
Section: Introductionmentioning
confidence: 99%